Innovative hydroxyapatite/bioactive glass composites processed by spark plasma sintering for bone tissue repair. Issue 4 (April 2017) - Bellucci, Devis; Desogus, Luca; Montinaro, Selena; Orrù, Roberto; Cao, Giacomo; Cannillo, Valeria
Abstract: Hydroxyapatite-based composites (HA-C) with bioglass as second phase are usually produced by hot-pressing or pressureless sintering. However, such methods require thermal levels which exceed the crystallization temperature of the glass, with possible negative effects on the bioactivity of the final system. Spark plasma sintering (SPS) is a powerful consolidation technique in terms of both processing time and temperature. In this work SPS has been employed, for the first time, to obtain HA-C with an innovative bioglass as second phase. Such glass was designed to be used whenever a thermal treatment is required, thanks to its low tendency to crystallize. A systematic study is conducted to identify the optimal sintering conditions for preparing highly dense composites and, at the same time, to minimize the crystallization of the glassy phase. The obtained samples are highly bioactive and display higher compactness and hardness with respect to the counterparts produced by conventional sintering methods.